Trade liberalization, consumption shifting and pollution: Evidence from Mexico's used vehicle imports - Liang Chen; Cecilia Garcia-Medina; Rui Wan (Banco de México, 2022)
This paper develops a model of used vehicle trade between countries with different environmental regulations regarding vehicle emissions. We show that the US, given its strict environmental regulations, has incentives to export used vehicles to Mexico, which impacts air pollution emissions caused by automobile driving in Mexico. Using a unique database on vehicle registration in Mexico and imports after the NAFTA enactment, we find that Mexico's used vehicle imports reduced average pollution emissions generated by vehicles, mainly due to the "technique effect"-differences in emissions of vehicles of comparable model and age between those that operate in the US before being imported (that emit less pollutants) and those operating in Mexico.
Keywords: F13; L62; Q56; Q51; 330; Trade Liberalization; Used Vehicles; Pollution Emissions; Technique Effect